Implementasi Buku Skrining dan Stimulasi Motorik kasar Anak Stunting Usia 0-60 Bulan Dalam Peningkatan Pemahaman Isu Stunting Masayarakt di Desa Mancasan - Farid Rahman; Tiara Fatmarizka; Taufik Eko Susilo; Qonitah Faizatul Fitriyah; Arzhuma Arza Lazuardy; Muhammad Mukhlis Cahyadi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Stunting, a chronic nutritional problem characterized by a child's height below the standard for his or her age, is still a challenge in Indonesia. According to data from the Ministry of Health, the prevalence of stunting in Indonesia in 2021 is 24.4%. In Mancasan Village the prevalence of stunting reached 24%. This figure is quite high, considering that stunting can have a negative impact on children's growth and development, both physically and cognitively. One effort to prevent stunting is to carry out early screening and provide gross motor stimulation. Stunting screening can be done using a screening book and motor stimulation for stunted children aged 0-60 months. This community service is carried out using educational methods, namely lectures and questions and answers. The results of community service show that there has been an increase in community understanding about screening and gross motor stimulation of children aged 0-60 months from 12.9% to 28.6%. It is hoped that this increase in community understanding can reduce the incidence of stunting in Mancasan Village.